Anesthetic care during posterior spinal fusion in a patient with Prader-Willi syndrome. - N. Rusin; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2020)
Prader-Willi syndrome (PWS), originally described in 1956, is a genomic imprinting disorder affecting chromo- some 15. Three genetic subtypes have been recognized, the most common of which is the paternal chromosome 15q11-q13 deletion accounting for 65-75% of cases. Pa- tients with PWS manifest several distinguishing charac- teristics including infantile hypotonia, cognitive dysfunc- tion, hyperphagia leading to obesity, short stature, ortho- pedic deformities, and hypothalamic dysfunction. Other important clinical manifestations include short stature, developmental delay, sleep disturbances including ob- structive sleep apnea, cognitive disabilities, seizures, be- havioral problems, and hypothalamic dysfunction. Due to associated end-organ involvement, surgical procedures are often required in PWS patients. We present a 12-year- old adolescent with Prader-Willi syndrome who required anesthetic care during a posterior spinal fusion to treat scoliosis. The potential periopera- tive implications of these patients are reviewed and op- tions for anesthetic care presented.